2002
DOI: 10.1021/jm011107f
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Derived Host Molecules as Reversal Agents for the Neuromuscular Blocker Rocuronium Bromide:  Synthesis and Structure−Activity Relationships

Abstract: A series of mono- and per-6-substituted cyclodextrin derivatives were synthesized as synthetic receptors (or host molecules) of rocuronium bromide, the most widely used neuromuscular blocker in anaesthesia. By forming host-guest complexes with rocuronium, these cyclodextrin derivatives reverse the muscle relaxation induced by rocuronium in vitro and in vivo and therefore can be used as reversal agents of the neuromuscular blocker to assist rapid recovery of patients after surgery. Because this supramolecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(143 citation statements)
references
References 24 publications
(57 reference statements)
2
140
0
1
Order By: Relevance
“…In a recent development, the γ-cyclodextrin sugammadex was chemically modified to encapsulate rocuronium and reverse neuromuscular blockade by forming a stable host-guest inclusion complex and removing the drug from the neuromuscular junction [87,88]. Whether encapsulation of rocuronium in this manner can mitigate an existing anaphylactic reaction induced by rocuronium remains to be proven but it has already been suggested that allergenicity may be retained due to incomplete encapsulation of the molecule in the inclusion complex form.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent development, the γ-cyclodextrin sugammadex was chemically modified to encapsulate rocuronium and reverse neuromuscular blockade by forming a stable host-guest inclusion complex and removing the drug from the neuromuscular junction [87,88]. Whether encapsulation of rocuronium in this manner can mitigate an existing anaphylactic reaction induced by rocuronium remains to be proven but it has already been suggested that allergenicity may be retained due to incomplete encapsulation of the molecule in the inclusion complex form.…”
Section: Discussionmentioning
confidence: 99%
“…We probed these ideas using cyclodextrins, cyclic sugar molecules with a hydrophobic core region within which cholesterol (Szejtli, 1998) and at least some steroids (Adam et al, 2002) fit. Cyclodextrins have been used to manipulate plasma membrane cholesterol content (Yancey et al, 1996;Haynes et al, 2000;Westover et al, 2003).…”
Section: Cyclodextrins Sequester Neurosteroidsmentioning
confidence: 99%
“…We hypothesized that the slow kinetics of these currents arises from accumulation of steroid into a reservoir, likely the plasma membrane, from which the ligand accesses a site on the GABA receptor. Support for this idea came from studies using ␥-cyclodextrin as a soluble, hydrophobic "sponge" (Adam et al, 2002). The presence of ␥-cyclodextrin significantly speeded the offset kinetics of directly gated neurosteroid currents.…”
Section: Introductionmentioning
confidence: 99%
“…HATU-mediated amide bond formation between 2ꞌ-aminoethyl-appended monosaccharides and the per-carboxyethylthio-terminated cyclodextrin derivatives 1 and 2 16 and the novel monocarboxy-derivative 7 (Scheme 1) gave the monodisperse products 3-6 and 8-9, respectively, whereas using HOBT/DCC coupling under numerous conditions (ratio, temperature, duration) products of inferior quality were obtained. The monosaccharides with 2ꞌ-aminoethyl linkers were synthesized according to literature methods from the parent monosaccharides: 2ꞌ-aminoethyl-α-D-mannopyranose was prepared in five steps and 59% overall yield 17 and 2ꞌ-aminoethyl-2-acetamide-2-deoxy-α-D-glucopyranose was prepared in three steps and 69% overall yield from the known azido precursor.…”
Section: Resultsmentioning
confidence: 99%